Physical and psychological wrestling performance: success predictors in female Olympic wrestling - López Gullón, José María; Torres Bonete, María Dolores; Berengüi, Rosendo; Díaz, Arturo; Martínez Moreno, Alfonso; Morales Baños, Vicente; García Pallarés, Jesús (Anales de Psicología / Annals of Psychology, 2012)
This study was undertaken to determine differences in physical, psychological and body composition variables related to success in female Olympic wrestling. Thirty five female freestyle wrestlers were assigned into two groups according to their competitive level: Elite (n=13) and Amateur (n=22). All subjects underwent an anthropometric assessment, a complete physical fitness test battery (maximal dynamic and isometric strength, muscle power output, crank-arm Wingate test, running speed and hamstring extensibility) as well as psychological characteristics assessment associated with sport performance through the Psychological Performance Inventory. Elite wrestlers were older, had more training experience, maximal dynamic and isometric strength, muscle power, mean and peak power during the crank-arm Wingate test, as well as lower percent body fat values. Furthermore, elite wrestlers showed significantly higher self-perceptions in the self-confidence scale. The present results suggest that several neuromuscular, anaerobic and psychological performance markers can be consider such as success predictors in female Olympic wrestling.